Interferon alpha and non-specific markers of inflammation in patients with systemic lupus erythematosus - Lamija Zečević; Edin Begić; Buena Aziri; Izeta Aganović-Mušinović (Medicinski glasnik, 2022)
Aim: To determine the value of IFN (intzerferon)-? in the patients with systemic lupus erythematosus (SLE) and to correlate IFN-? with values of non-specific biochemical parameters of inflammation (C-reactive protein, leukocytes values, erythrocyte sedimentation rate, albumins and globulins). Methods: Research included 55 patients with SLE diagnosis and a control group consisted of 25 healthy subjects (during period 2019-2020). IFN (Interferon)-? and non-specific biochemical parameters of inflammation were obtained using standard protocols. Results: IFN-? values were independent of gender (p=0.95). The difference in serum IFN-? values in relation with the age in the SLE group was statistically significant (p=0.036). Only serum globulin was significantly higher (p=0.0023) in IFN-? positive compared to IFN-? negative SLE patients. A statistically significant correlation between the values of IFN-? and globulin was proved (r=0.315; p=0.019). No significant correlation was found between other non-specific biochemical parameters and IFN-? values. Conclusion: Increased IFN-? values were observed in younger patients, and the correlation between IFN and globulin was proved.
Keywords: immunity; inflammation; interferon-alpha